If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = (5x + 6)(x + -9) Reorder the terms: 0 = (6 + 5x)(x + -9) Reorder the terms: 0 = (6 + 5x)(-9 + x) Multiply (6 + 5x) * (-9 + x) 0 = (6(-9 + x) + 5x * (-9 + x)) 0 = ((-9 * 6 + x * 6) + 5x * (-9 + x)) 0 = ((-54 + 6x) + 5x * (-9 + x)) 0 = (-54 + 6x + (-9 * 5x + x * 5x)) 0 = (-54 + 6x + (-45x + 5x2)) Combine like terms: 6x + -45x = -39x 0 = (-54 + -39x + 5x2) Solving 0 = -54 + -39x + 5x2 Solving for variable 'x'. Combine like terms: 0 + 54 = 54 54 + 39x + -5x2 = -54 + -39x + 5x2 + 54 + 39x + -5x2 Reorder the terms: 54 + 39x + -5x2 = -54 + 54 + -39x + 39x + 5x2 + -5x2 Combine like terms: -54 + 54 = 0 54 + 39x + -5x2 = 0 + -39x + 39x + 5x2 + -5x2 54 + 39x + -5x2 = -39x + 39x + 5x2 + -5x2 Combine like terms: -39x + 39x = 0 54 + 39x + -5x2 = 0 + 5x2 + -5x2 54 + 39x + -5x2 = 5x2 + -5x2 Combine like terms: 5x2 + -5x2 = 0 54 + 39x + -5x2 = 0 Factor a trinomial. (9 + -1x)(6 + 5x) = 0Subproblem 1
Set the factor '(9 + -1x)' equal to zero and attempt to solve: Simplifying 9 + -1x = 0 Solving 9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -1x = 0 + -9 -1x = 0 + -9 Combine like terms: 0 + -9 = -9 -1x = -9 Divide each side by '-1'. x = 9 Simplifying x = 9Subproblem 2
Set the factor '(6 + 5x)' equal to zero and attempt to solve: Simplifying 6 + 5x = 0 Solving 6 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 5x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 5x = 0 + -6 5x = 0 + -6 Combine like terms: 0 + -6 = -6 5x = -6 Divide each side by '5'. x = -1.2 Simplifying x = -1.2Solution
x = {9, -1.2}
| 5xy+y=0 | | 9(x-3)-6=2(x+5)+13 | | 0=(4x+3)(x-5) | | 4x+6=-5+2x+15 | | 3x^4-6x^3+3=0 | | (x*x)+3x=(x*x)+x | | 5x+20=7x-80 | | (x*x)+3x=(x*x)+x+2 | | 7log(2x+12)=14 | | 7x-3x=15-5 | | (3x^2+2x)+(3x-12)=0 | | 6.6n-60=220 | | 2a-2b=10 | | 2x-37=50 | | 4.2x+35.4=9.8-8.6x | | 0=(8x+9)(x-5) | | 6x=22+4x | | -15=3a-3 | | 8x+35.4=9.8-8.6x | | a^2-1=-7a | | (2x-3)-(x-2)=1 | | x^2-22x+66=0 | | 6x+2=6(x+8) | | y=(7x+6)(x-4) | | 12x+48y-42= | | 5v+40=4v+50 | | 6x+19y=1 | | 12k^2-21=0 | | A=3.14(25) | | 3x-2(2x+2)=5 | | 25v^2=9 | | 2b-4=-6 |